STRATEGI MENINGKATKAN EFISINESI DAN EFEKTIVITAS KINERJA KEUANGAN PEMERINTAH KOTA BOGOR DALAM PENGELOLAAN APBD - Syauqi, Muhamad; Siregar, Hermanto; Syaukat, Yusman (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2017)
ABSTRACT Financial performance and budgetary realization is one of the most important keys into the progress of an organization. Hhealthy or not can be marked from the financial performance that showed by the financial statements, that’s would be the source of organizational decisions in the future of financial side. The purpose of this research to analysis the finance performance of Bogor city government that measured with regional finance ratio, identifies the factors are affecting finance performance Bogor city ggovernment, formulate the strategies and policies in order to increasing efficiency and effectiveness the finance performance of Bogor city government in managing of the budgetary of regional revenue and expenditure. This research applied descriptive analysis, quantitatively using multiple regression method and analytical hierarchy process. The result makes the point that the finance performance of Bogor city government has unstable yet. This measured by the indicator i.e less fiscal decentralization has given dependency to the central government very high. There have the variables influence between investment, percapita income, local taxes that had a positive and gross regional domestic product (PDRB) has a negative impact also significant influence toward the financial performance. The priority sequences of strategies to improve the efficiency and effectiveness of Bogor Government finance performance with analytical hierarchy process method as follows: (1) increasing the supervision; (2) education and training; (3) communication and commitment to achieve the goals; (4) implementation the incentive and disincentive regulations; (5) intensification and intensification of taxes and local retributionKeywords: Efficiency and Effectiveness, Financial Performance, Bogor City Government, Budgetary of Regional Revenue and ExpenditureABSTRAKKinerja keuangan dan realisasi anggaran merupakan salah satu kunci dalam kemajuan suatu organisasi. Sehat atau tidaknya suatu organisasi dapat dinilai dari kinerja keuangan ditunjukkan oleh laporan keuangan, hal itu yang akan menjadi sumber keputusan organisasi di masa mendatang dari sisi finansial. Tujuan dari penelitian ini adalah menganalisis kinerja keuangan pemerintah Kota Bogor yang diukur dengan rasio keuangan daerah, mengindentifikasi faktor-faktor yang mempengaruhi kinerja keuangan pemerintah Kota Bogor, merumuskan strategi dan kebijkan untuk meningkatkan efisiensi dan efektivitas kinerja keuangan pemerintah Kota Bogor dalam pengelolaan APBD. Penelitian ini menggunakan analisis deskriptif, analisis kuantitatif menggunakan metode regresi linier berganda dan AHP. Hasilnya menunjukkan bahwa kinerja keuangan pemerintah Kota Bogor belum stabil. Hal ini ditunjukkan oleh indikator desentralisasi fiskal kurang mengingat ketergantungan keuangan terhadap pemerintah pusat sangat tinggi. Ada pengaruh antara variabel investasi, pendapatan perkapita, pajak daerah mempunyai pengaruh yang positif dan PDRB mempunyai pengaruh yang negatif signifikan terhadap kinerja keuangan. Urutan prioritas strategi meningkatkan efisiensi dan efektivitas kinerja keuangan pemerintah Kota Bogor dengan metode AHP adalah sebagai berikut: 1. meningkatkan pengawasan, 2. Pendidikan dan pelatihan, 3. komunikasi dan komitmen pencapaian sasaran, 4. penerapan regulasi insentif dan disinsentif, 5.intensifikasi dan ekstensifikasi pajak dan retribusi daerah. Kata Kunci: Efisiensi Dan Efektivitas, Kinerja Keuangan, Pemerintah Kota Bogor, APBD